Penerapan Media Boneka Jari Dalam Mengembangkan Kemampuan Berbicara Anak PAUD Mawar Sebambang Sambas - Saripah; Azwar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
Basically, children are born naturally, and have their own identity. The language that children have is still vulnerable in not being clear. And this needs to be improved for language development towards adulthood. Learning for early childhood should be fun and not boring. So that children are comfortable in the learning process. This study uses a descriptive qualitative research type with the aim of describing the development of early childhood speech skills at PAUD Mawar Sebambang through the medium of finger puppets. The subjects of this study were group A children and the teachers of the Mawar Sebambang PAUD class. Data collection techniques used in this study are observation, interviews, and documentation. The results of research on the application of finger puppet media in developing the speaking skills of early childhood at Mawar Sebambang PAUD show that children are more active when learning activities, especially speaking activities with finger puppet media. It is easier for teachers to interact with children when using finger puppet media as a support in the process of learning activities.